(untitled) (مجلة الهندسة, 2007)
The mathematical model of the tapered struts subjected to axial load is solved to obtain the modified stability functions due to shear effect as well as bending effects. The stability functions are derived for a wide range of non-prismatic struts then compared in graphical curves with stability functions excluding shear effects. The stability functions for non-prismatic members under compressive and tensile axial loads are developed for the purpose of expressing both effects of bending and shear in a beamcolumn stiffness at any value of axial force under the buckling limit